A Study of The Socio-Economic Hurdles Experienced During The COVID-19 in South Africa - Ncana, Nzuzo; Kang’ethe, Simon Murote (Indonesian Journal of Social Research (IJSR), 2025)
The pandemic imposed a weighty socio-economic quagmire that left the residents of Joza township economically disenfranchised. The study adopted a qualitative approach and phenomenology as a specific design, with data collected from semi-structured interviews. Joza residents faced various socio-economic hurdles, which included economic decline due to the COVID-19 pandemic. The economic decline led to increased unemployment, which subjected more families to poverty. Another socio-economic hurdle that this study uncovered was the increased cost of living during the pandemic, which made many families unable to afford basic needs such as food and clothing, hence exposing many children to malnutrition. The study found that some companies resorted to retrenchments as they were not making a profit due to unfavorable economic conditions, and that led to job losses and increased crime involvement among youth. Women from previously disadvantaged communities were the most affected by the socio-economic hurdles of the COVID-19 epoch. This paper recommends that the government must increase the COVID-19 Social Relief Grant to meet the poverty line and make it permanent; the government should also strengthen support of Small, Medium, and Micro Enterprises (SMMEs) by providing more financial support to these Enterprises and encouraging them to employ youth and women. This will help reduce crime among youth and poverty among families